2021
DOI: 10.3390/su13158627
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Entrepreneurial Intentions: A Mediation-Moderation Perspective

Abstract: This research was aimed to investigate the connection between the social networking sites and green entrepreneurship intentions through a mediated-moderated model. The study was based on the Shepero’s model of entrepreneurship intentions and Ajzen’s theory of planned behavior. The study design reflects that social networking sites and green entrepreneurship intentions are mediated by risk propensity and self-efficacy, while self-efficacy and green entrepreneurship intentions’ relationship is further moderated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
(59 reference statements)
4
19
0
4
Order By: Relevance
“…According to an empirical literature study, the application of GESI business played an important role in overcoming poverty, unemployment, inequality, food insecurity, and environmental degradation in Africa (Slavova & Heuër, 2015). Another report explained that a significant positive correlation was observed between social networking sites and green entrepreneurial intentions, through indirect effects of risk and self-efficacy in Pakistan (Hussain et al, 2021). This confirmed that the roles of government and private institutions worked comprehensively to spread the green wave among aspiring business insiders (Hussain et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 78%
“…According to an empirical literature study, the application of GESI business played an important role in overcoming poverty, unemployment, inequality, food insecurity, and environmental degradation in Africa (Slavova & Heuër, 2015). Another report explained that a significant positive correlation was observed between social networking sites and green entrepreneurial intentions, through indirect effects of risk and self-efficacy in Pakistan (Hussain et al, 2021). This confirmed that the roles of government and private institutions worked comprehensively to spread the green wave among aspiring business insiders (Hussain et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 78%
“…The use of ICT tools and Industry 4.0 eases the information flow through the network, thus improving the sustainability of the food supply chain (Routroy & Behera, 2017 ). Hussain et al ( 2021 ) explain that there is a significant link between updated technologies (social networking platforms) with sustainable practices. Thus, in order to have a sustainable food supply chain smart technologies and social networking apps need to be installed.…”
Section: Resultsmentioning
confidence: 99%
“… Ye et al (2020) elucidated that the normative environment is a significant factor to yield entrepreneurial activities in society. On the contrary, Hussain et al (2021) anticipated that subjective norms have no association with green entrepreneurship. Chen et al (2018) put forward that knowledge has the key factor to influence green entrepreneurs’ activities which is similar to the present study model.…”
Section: Discussion and Implicationmentioning
confidence: 99%